Development of an improved camping grill / Nur Aliah Afifah Mohd Shahril - Mohd Shahril, Nur Aliah Afifah (2024)
Nowadays, camping has been one of the most popular outdoor activities. For campers, a camping grill is one of the most important must-have camping gear they need to consider as it must be portable and foldable, hence easy to carry and travel outdoors. Before this, campers only brought a piece of net and had a burning activity directly to the ground, causing harm to our environment. Therefore, this study aims to design a product that can help users mostly campers, carry a camping grill, and spacesaving using a mechanical engineering design process. The modeling for this product was developed by using SolidWorks software. The product focused on a camping grill with portable and foldable features. In addition, it has a compartment that can hold charcoal and wood-burning waste without contaminating the ground. At the end of the study, this camping grill helped not only the users but also became an environmentally friendly product.